RETRACTED: MiR-22 Inhibition Alleviates Cardiac Dysfunction in Doxorubicin-Induced Cardiomyopathy by Targeting the sirt1/PGC-1α Pathway - Wang, Runze; Xu, Yuerong; Niu, Xiaolin; Fang, Yexian; Guo, Dong; Chen, Jiangwei; Zhu, Hanzhao; Dong, Jiaying; Zhao, Ran; Wang, Ying; Qi, Bingchao; Ren, Gaotong; et al. (Frontiers in Physiology, 2021)
Doxorubicin cardiotoxicity is a life-threatening side effect that leads to a poor prognosis in patients receiving chemotherapy. We investigated the role of miR-22 in doxorubicin-induced cardiomyopathy and the underlying mechanism in vivo and in vitro. Specifically, we designed loss-of-function and gain-of-function experiments to identify the role of miR-22 in doxorubicin-induced cardiomyopathy. Our data suggested that inhibiting miR-22 alleviated cardiac fibrosis and cardiac dysfunction induced by doxorubicin. In addition, inhibiting miR-22 mitigated mitochondrial dysfunction through the sirt1/PGC-1α pathway. Knocking out miR-22 enhanced mitochondrial biogenesis, as evidenced by increased PGC-1α, TFAM and NRF-1 expression in vivo. Furthermore, knocking out miR-22 rescued mitophagy, which was confirmed by increased expression of PINK1 and parkin and by the colocalization of LC3 and mitochondria. These protective effects were abolished by overexpressing miR-22. In conclusion, miR-22 may represent a new target to alleviate cardiac dysfunction in doxorubicin-induced cardiomyopathy and improve prognosis in patients receiving chemotherapy.